Reliability Analysis and Maintainability for the Design of Grid and Hybrid Solar Power Plant Systems in Wonogiri Regency - Nur’Aini, Etika; Budiarto, Rachmawan; Setiawan, Bakti; Ma'arif, Alfian (Faculty of Engineering, Universitas Tanjungpura, 2021)
Indonesia has the potential for large solar power plants. It has relatively constant solar radiation because it is close to the equator. Besides, solar energy includes renewable energy that is more environmentally friendly and easier to apply in office areas, especially Wonogiri. However, it turns out that the solar power plant projects that have been built are not yet fully functional, and some have even failed. A lack of responsibility and maintenance causes this carried out after the project is complete. For this reason, it is necessary to estimate the reliability of these components and determine the maintenance schedule before the project is carried out. So that later they have a picture and be better prepared when this project is already underway. The fault tree method's failure factors are expected to create a picture to maintain reliability and determine the prioritized components for maintainability. For the results obtained to be more appropriate, apart from seeing the quantitative analysis output, the fault tree also needs to be adjusted to the component manual or datasheet to determine the replacement of spare parts and their maintenance. So that the resulting schedule for maintenance and replacement of spare parts. Thus, the solar power plant project that has been built will be more reliable and can be appropriately utilized.